Albania’s Trade Specialization and its Economic Growth Perspective in the Future. - Mitaj, Arjola; Muco, Klodian; Avdulaj, Jonida (European Journal of Sustainable Development, 2014)
Starting from 1992, the Albanian economy has experienced a gradual openness. Initially, it was applied for the first time, the structural adjustment program which contained some basic aspects such as: a restrictive monetary policy for inflation control, liberalization of the economy and prices, public enterprises privatization in order to restructure and attract foreign investments, full market liberalization. It was also adopted the "open gate" policy that means a progressive opening of the country to foreign investment, which was based on comparative advantages of Albanian economic system, or more precisely on the low cost of labor force which is estimated at 90 cent for the fasson sector and call-center service, groundwater resources, its geographical position with access to both Adriatic and Ionian sea. Based on the above facts, this paper will try to make an empirical analysis of comparative advantages of Albania, taking into account the degree of international trade openness and Balassa revealed comparative advantage (RCA). It will also be analyzed the structure of Albanian international trade and its production specialization in order to give some information on the future economic specialization of our country and help policy makers to orient economic development policies. Keywords: foreign trade, economic development, commercial specialization.